Perancangan Perancangan Dan Penjadwalan Penambangan Tahun 2023 Di Pit 3 PT. Mutiara Fortuna Raya 180 Kabupaten Muaro Jambi - putra, brian khurohmad; Yulanda, Yudi Arista; Prabawa, Aditya Denny (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2024)
PT Mutiara Fortuna Raya's mining operations are currently guided by an annual mining design without detailed mining scheduling. However, variations in mining direction and sequence can lead to discrepancies in coal expose achievement, ultimately impacting coal production outcomes. High SR locations demand a more overburden volume and time. This research aims to evaluate various mining direction options to determine the most optimal approach. The research methodology uses a quantitative approach, comparing three mining scheduling scenarios: panel scenario, strip scenario, and block scenario. These scenarios are based on the 2023 reserve design results of 180,518 tons coal and 385,390 BCM of overburden. The outcomes of these three scenarios reveal varying stripping ratios across each period. Stripping ratio for the panel scenario: Quarter I SR 10.84, Quarter II SR 4.77, Quarter III SR 1.64, and Quarter IV SR 0.20. Stripping ratio for the strip scenario: Quarter I SR 5.11, Quarter II SR 2.40, Quarter III SR 1.67, and Quarter IV SR 0.53. Stripping ratio for the block scenario: Quarter I SR 8.93, Quarter II SR 3.10, Quarter III SR 1.74, and Quarter IV SR 0.21. Analysis of three scenarios indicates that block scenario presents the most favorable schedulling for implementation.